The management of aerial particulate pollution : the case of Platinum Industry Smelters in the Rustenburg region of North West Province, South Africa - Meiklejohn, K.I. (Ian) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2006.